Graded bulk-heterojunction enables 17% binary organic solar cells via nonhalogenated open air coating - Ying Zhang (Nature Portfolio, 2021)
Graded bulk-heterojunction organic solar cell with well-defined vertical phase separation has the potential to surpass the classical counterpart, thus the optimisation of this structure is crucial. Here, the authors reveal solvent selection strategies for optimising morphology of the structure, enabling efficient, eco-friendly, and scalable solar cells.